Have not - Western, Blaine; Rönkä, Eeva; Föll, Heike-Karin 1967-; Knes, Heinz Peter 1969-; Loschert, Kristin 1979-; Etiman, Yusuf 19XX- (BOM DIA BOA TARDE BOA NOITE, 2017)
have not is a collation of stories and memories that inhere in time-worn clothing. The clothing in have not is contextualised by the history and conditions of its appearance, or, alternately the stories and memories that constitute its persistence and resonance in the present. have not variously reflects the modes of presentation native to fashion magazines and yet it loosens these conventions from the urgencies and patterns of pressurised pitches and targeted sales. have not is a fashion magazine unstuck in time; without a mandate to reflect and report exclusively on the contemporary, have not recounts the utterances that persist beyond the material accoutrements of our lives in the present. have not is: borrowed, lost, missed, longed, described, collected, collated, archived, affected, referenced, remembered, modelled, uncompleted, impressed, desired, endured.
700 copies
Keywords: Kleidung; Ästhetik; Gebrauchtware; Selbstverständnis; Kunst; Clothing; Contemporary art; Fashion; Bildband